Outcomes of Complete and Early Vitrectomy in Post-Operative Endophthalmitis After Cataract Surgery - Arain, Muhammad Aamir; Muzaffar, Waqar; Farooq, Omer; Azhar, Muhammad Naeem (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the outcomes after complete and early micro-incision vitrectomy surgery in patients with postoperative endophthalmitis after cataract surgery. Study Design: Quasi-experimental study. Place and Duration of Study: Vitreoretina Department, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jul 2017 to Dec 2020. Methodology: Thirty (30) patients diagnosed with post-operative endophthalmitis after cataract surgery were included in the study. A vitreous sample was taken and sent for bacterial and fungal culture. A complete vitrectomy was performed after induction of posterior vitreous detachment. The peripheral vitreous base was trimmed, followed by intravitreal antibiotics. Patients were followed up on the first post-operative day and followed up at one week, month and three months. At three months follow-ups, the best corrected visual acuity was noted. Success was defined as best corrected visual acuity (BCVA) of ≥6/60, while failure was defined as BCVA <6/60 three months after vitrectomy. Results: Mean age of patients was 61.33±14.38 years. Average time from onset of symptoms of endophthalmitis to vitrectomy was 13.46±9.99 days. Pre-operatively one patient had BCVA ≥6/60, and 29 patients had BCVA <6/60, whereas postoperatively, 25 patients had BCVA≥6/60, and 5 patients had BCVA<6/60. This difference was statistically significant (p<0.001). Conclusion: Complete and early vitrectomy is safe and effective in managing post-operative endophthalmitis with better visual outcomes.